2015
DOI: 10.1093/ve/vev015
|View full text |Cite
|
Sign up to set email alerts
|

Role of the host restriction factor APOBEC3 on papillomavirus evolution

Abstract: More than 270 different types of papillomaviruses have been discovered in a wide array of animal species. Despite the great diversity of papillomaviruses, little is known about the evolutionary processes that drive host tropism and the emergence of oncogenic genotypes. Although host defense mechanisms have evolved to interfere with various aspects of a virus life cycle, viruses have also coevolved copious strategies to avoid host antiviral restriction. Our and other studies have shown that the cytidine deamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 71 publications
10
86
0
Order By: Relevance
“…It is unclear whether the virus directly induces the A3B response to such a level as to avoid restriction while generating additional genetic diversity for better fitness as has been observed in HIV-1 (40,41). Our data are also consistent with recent reports that point to possible roles of A3 enzymes during HPV evolution (42). Interestingly, we also identified a strong asymmetry in the abundance TC or its reverse complement GA that corresponds to the direction of both transcription and viral genomic DNA lagging-strand replication.…”
Section: Discussionsupporting
confidence: 86%
“…It is unclear whether the virus directly induces the A3B response to such a level as to avoid restriction while generating additional genetic diversity for better fitness as has been observed in HIV-1 (40,41). Our data are also consistent with recent reports that point to possible roles of A3 enzymes during HPV evolution (42). Interestingly, we also identified a strong asymmetry in the abundance TC or its reverse complement GA that corresponds to the direction of both transcription and viral genomic DNA lagging-strand replication.…”
Section: Discussionsupporting
confidence: 86%
“…However, since TLR9 expression is significantly downregulated in cells expressing the HPV oncoprotein E7 as described above, it is likely that HPV infection and viral gene expression may be influenced by TLR9 responses. Similar to many other small DNA viruses, such as adenovirus and parvovirus, papillomavirus genomes have significantly lower contents of CpG dinucleotides than expected by random chance (Upadhyay et al, 2013; Upadhyay and Vivekanandan, 2015; Warren et al, 2015a). In a recent publication, we calculated the ratio of observed vs. expected (O/E) counts of all dinucleotides in the genomes of all 274 PVs deposited in the Papillomavirus Episteme (PaVE) database (Warren et al, 2015a).…”
Section: Roles Of Host Defense In Papillomavirus Genome Evolutionmentioning
confidence: 88%
“…Similar to many other small DNA viruses, such as adenovirus and parvovirus, papillomavirus genomes have significantly lower contents of CpG dinucleotides than expected by random chance (Upadhyay et al, 2013; Upadhyay and Vivekanandan, 2015; Warren et al, 2015a). In a recent publication, we calculated the ratio of observed vs. expected (O/E) counts of all dinucleotides in the genomes of all 274 PVs deposited in the Papillomavirus Episteme (PaVE) database (Warren et al, 2015a). We revealed that CpG dinucleotides are the most underrepresented dinucleotide in the genomes of all PV types, except two bird PVs.…”
Section: Roles Of Host Defense In Papillomavirus Genome Evolutionmentioning
confidence: 88%
See 1 more Smart Citation
“…Long-term expression of (virally transduced) transgenes is an active field of study1213, but it has been shown that CpG motifs located within the promoter and/or open reading frame (ORF) are associated with a loss of transgene expression1415. Furthermore, the HPV18 genome has a decreased CpG content16, suggesting that CpG motifs may affect the fitness of these viruses17.…”
Section: Resultsmentioning
confidence: 99%